Strategic change: a journey towards new meaning? Semantic analysis of corporate communication - Malin Olander Roese; Sverker Sikström (International Journal of Business Science & Applied Management (IJBSAM), 2014)
Strategic change, infused with new data, perspectives and concepts may change the inherent meaning of the central tenets in an existing strategy. It taps into the cognitive aspects of a journey where language, in verbal and written form, aids in the process of communicating, understanding and creating new meaning. Hence, it comes as no surprise that communication is argued to be an important means of forming and executing strategy, particularly if that strategy involves change. Thus far corporate communication has been the objective of extensive and predominately qualitative analysis of written content, with a focus on identifying and demonstrating strategic intent or reorientation. The objective here is to take a different route, not yet explored in the field of strategic management and change. Leaning on a previously conducted, longitudinal and qualitative case study of strategic change the aim is twofold: Firstly, to propose a method for quantitative analysis of semantic content of texts and statistically test the semantic development over time in the same case. Secondly, to evaluate and discuss the results of a quantitative semantic analysis in relation to previous and qualitative findings. By applying latent semantic analysis (LSA), we quantified the semantic content of annual reports and press releases between 2001 and 2010, derived from a case study of one company in the paper packaging industry. Using this method, we statistically analysed significant changes in semantic content across the ten-year time period studied. The results indicate interesting avenues for continued and wider use of quantitative semantic analysis in contributing to the understanding of semantic development and strategic change.
Keywords: 650; strategic change; communication; cognition; latent semantic analysis; paper packaging industry